Nowe instrumenty polityki spójności Unii Europejskiej na lata 2007-2013 - Ryszawska-Grzeszczak, Bożena (The New Instruments of European Cohesion Policy (2007-2013), 2007)
The European Commission has established three instruments for new member countries supporting implementation of Cohesion Policy priorities. "The Cohesion Policy in support of growth and jobs, immunity strategic guidelines 2007-2013" stresses the importance of improving access to finance for ¡development of Small and Medium Enterprises JEREMIE (Joint European Resources for Micro and Idiom Enterprises), for cities which play a key role in implementing the growth and job strategy in (regions JESSICA (Joint European Support for Sustainable Investment in City Areas) and also for t infrastructure projects in new member countries JASPERS (Joint Assistance in Supporting Projects I European Regions). The programmes will set out objectives and the relevant grant resources specifically for action to improve access to finance based on the gap analysis in different areas.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 338-347